Key trends in modern management - Krasnokutska, N. S. (NTU "KhPI", 2017)
The study has shown the major trends that affect the creation and spread of new methods of management in the information society.The attained results prove the fact that precisely because of the efforts of managers companies can take their rightful place in the business environment, even at the low level of physical resources.
Keywords: management; globalization; corporate social responsibility; psychological methods; organizational ecosystems; information society